Implementasi program pemberdayaan desa melalui Usaha Ekonomi Desa Simpan Pinjam (UED-SP): Analisis maqasid al-syari'ah di Kabupaten Indragiri Hilir - Siti Aisyah; Sofyan Sulaiman (AL-Muqayyad, 2026)
This study analyzes the implementation of the Village Empowerment Program through the Village Savings and Loan Enterprise (UED-SP) in Indragiri Hilir Regency from the perspective of maqasid al-syariah. Unlike previous studies focusing primarily on program effectiveness, this research evaluates both institutional governance and financing practices based on Islamic economic principles. This qualitative field study employed purposive sampling. Data were collected through in-depth interviews, observations, documentation, and literature review and analyzed using the interactive model, consisting of data condensation, data display, and conclusion drawing/verification. The findings show that UED-SP has strengthened rural economic empowerment through productive financing, social programs, and institutional capacity building. However, its financing mechanism still applies an interest-based system, which is inconsistent with maqasid al-syariah, particularly the protection of wealth (ḥifẓ al-māl). This study contributes to Islamic economics by demonstrating that effective village empowerment requires both sound institutional governance and Sharia-compliant financing. It recommends adopting Sharia-based contracts to promote sustainable, equitable, and Sharia-oriented rural development.